Visual Field Progression in the Collaborative Initial Glaucoma Treatment Study : The Impact of Treatment and Other Baseline Factors - MUSCH, David C; GILLESPIE, Brenda W; LICHTER, Paul R; NIZIOL, Leslie M; JANZ, Nancy K (Ophthalmology (Rochester, Minn.), 2009)
To evaluate factors associated with visual field (VF) progression, using all available follow-up through 9 years after treatment initiation, in the Collaborative Initial Glaucoma Treatment Study (CIGTS). Longitudinal follow-up of participants enrolled in a randomized clinical trial. Six hundred seven newly diagnosed glaucoma patients. In a randomized clinical trial, 607 subjects with newly diagnosed open-angle glaucoma initially were treated with either medication or trabeculectomy. After treatment initiation and early follow-up, subjects were evaluated clinically at 6-month intervals. Study participants in both arms of the CIGTS were treated aggressively in an effort to reduce intraocular pressure (IOP) to a level at or below a predetermined, eye-specific target pressure. Visual field progression was analyzed using repeated measures models. Visual field progression, measured by Humphrey 24-2 full-threshold testing and assessed by the change in the mean deviation (MD), and an indicator of substantial worsening of the VF (MD decrease of > or =3 dB from baseline), assessed at each follow-up visit. Follow-up indicated minimal change from baseline in each initial treatment group's average MD. However, at the 8-year follow-up examination, substantial worsening (> or =3 dB) of MD from baseline was found in 21.3% and 25.5% of the initial surgery and initial medicine groups, respectively. The effect of initial treatment on subsequent VF loss was modified by time (P<0.0001), baseline MD (P = 0.03), and diabetes (P = 0.01). Initial surgery led to less VF progression than initial medicine in subjects with advanced VF loss at baseline, whereas subjects with diabetes had more VF loss over time if treated initially with surgery. The CIGTS intervention protocol led to a lowering of IOP that persisted over time in both treatment groups. Progression in VF loss was seen in a subset, increasing to more than 20% of the subjects. The findings regarding initial surgery being beneficial for subjects with more advanced VF loss at presentation, but detrimental for patients with diabetes, are noteworthy and warrant independent confirmation. The author(s) have no proprietary or commercial interest in any materials discussed in this article.